2003
DOI: 10.1212/01.wnl.0000042084.03066.c0
|View full text |Cite
|
Sign up to set email alerts
|

Mirtazapine induces REM sleep behavior disorder (RBD) in parkinsonism

Abstract: Shortly after initiation of mirtazapine (a noradrenergic and serotonergic antidepressant) treatment in four patients with parkinsonism, the authors observed the appearance of REM sleep behavior disorder (RBD). In the two patients with severe motor symptoms, RBD was accompanied by hallucinations and confusion. These disturbances resolved with drug discontinuation, and remained resolved by 12- to 24-month follow-up, suggesting that RBD can be triggered by a drug lacking anticholinergic activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
49
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 112 publications
(49 citation statements)
references
References 19 publications
0
49
0
Order By: Relevance
“…There are a few recent reports on RBD associated with spinocerebellar atrophy type 3 (Machado-Joseph disease). [63][64][65] As noted above, numerous cases of RBD have been reported in conjunction with MSA, 3,22,23,27,[66][67][68][69][70][71][72] PD, 3,11,22,[24][25][26][27][30][31][32][33][34][35]73 and DLB. 1,10,15,41,45,[47][48][49][50][51][52][53]55,59,60,74 Although frequency data on the presence of RSWA and RBD in the neurodegenerative disorders is based on relatively small numbers of patients thus far, the presence of each in MSA has been reported to be 90% to 95% for RSWA and 68% to 90% for RBD, 66,67 and presence of each in PD is approximately 58% for RSWA and 33% for RBD.…”
Section: The Rbd-synucleinopathy Associationmentioning
confidence: 99%
“…There are a few recent reports on RBD associated with spinocerebellar atrophy type 3 (Machado-Joseph disease). [63][64][65] As noted above, numerous cases of RBD have been reported in conjunction with MSA, 3,22,23,27,[66][67][68][69][70][71][72] PD, 3,11,22,[24][25][26][27][30][31][32][33][34][35]73 and DLB. 1,10,15,41,45,[47][48][49][50][51][52][53]55,59,60,74 Although frequency data on the presence of RSWA and RBD in the neurodegenerative disorders is based on relatively small numbers of patients thus far, the presence of each in MSA has been reported to be 90% to 95% for RSWA and 68% to 90% for RBD, 66,67 and presence of each in PD is approximately 58% for RSWA and 33% for RBD.…”
Section: The Rbd-synucleinopathy Associationmentioning
confidence: 99%
“…1,2 It has been increasingly reported among psychiatric populations and has a potential association with use of psychotropics, particularly selective serotonin reuptake inhibitor (SSRI), tricyclic, and serotonin and noradrenergic reuptake inhibitor (SNRI) antidepressants. [3][4][5][6][7][8] A previous case report 5 found that cessation of SSRI treatment did not result in complete resolution of clinical RBD symptoms and polysomnographic (PSG) abnormalities. Our recent clinical epidemiologic study 8 found that 3.8% of psychiatric outpatients might have RBD features over the past year.…”
mentioning
confidence: 99%
“…He never presented any episodes of RBD before the operation day, nor during the nearly 3-year postoperative period. He was not treated by mirtazapine known to induce RBD in Parkinsonism [8]. As a disorder of the dopaminergic pathway has been suggested to play a role in RBD (see Introduction), one could suspect that the decrease in dopamine treatment, carried out in the pre-operative period in our patient, could be a precipitating factor.…”
Section: Discussionmentioning
confidence: 90%